O comportamento respiratório e a cascata de O2 no cascudo de respiração bimodal Pterygoplichthys anisitsi (Teleostei, Loricariidae) - Cruz, André Luis da (Universidade Federal de São Carlos, 2007)
The condition of poor oxygen, called hypoxia, can affect aquatic environments. Their cause can be natural or, more frequently, a consequence of anthropogenic action. Among fish, the Siluriformes group (catfishes and armoured catfishes) contains hypoxic-tolerant species, being considered interesting experimental models. This study utilized the air-breathing armoured catfish Pterygoplichthys anisitsi, with the objective to analyze its respiratory physiology, at aquatic and air respiration, submitted to experimental conditions of hypoxia and air exposure to compare its respiratory behaviour and oxygen transport cascade steps (ventilatory, morphofunctional, haemoglobin and metabolic aspects). From all these experiments it can be concluded that gills respiratory surface is much more developed than stomach s surface, which indicates dependency on aquatic respiration. Furthermore, the air-breathing organ serves as an air reservatory that can assure the tolerance to reduced oxygen availability in the water. It was verified that the air-breathing behaviour is continuous, in non regular periods, but not obligatory and, even in normoxia, its more frequently occurs at night and in synchronic episodes, probably consisting in an antipredatory behaviour. In exposure to hypoxia and without access to atmospheric air, the reduction in metabolic rate and O2 extraction, the stomach supports the oxy-conformist behaviour that is characterized by apnoea with the gradual reduction of oxygen tension. The association among a stomach air reservatory, the continuous, but non-obligatory air breathing, an oxy-conformist behaviour characterized by apnoea, the presence of an haemoglobin cathodic component, and a higher haemoglobin-oxygen affinity in hypoxia perform necessary adjustments to hypoxia conditions. Moreover, the haematological parameters increase hypoxia tolerance, since hemoconcentration contribute to the enhanced capacity of O2 transportation in response to the increased demand and, therefore, result in a higher haemoglobin-oxygen affinity. With the decrease of metabolic rate and O2 extraction, there is the activation of anaerobic metabolism by fermentative process to maintain the energetic supply. Differently from hypoxia condition, the gills do not seem to be functional during air exposure, given that it was not observed a water flow through branchial filaments and, thus the stomach surface can be considered the respiratory organ in this condition. When exposed to air, periods of intermittent inspiration and expiration behaviour through the mouth are verified in order to supply air to the stomach. Additionally, haemoglobin-oxygen affinity is similar to that observed in normoxia and, in the same way, there is not alteration on haematological parameters. These observations indicate the functionality of stomach as a respiratory surface and the maintenance of aerobic metabolism. However, air exposure is a stressful condition, as it can be proved by the reduction of hepatic and muscular glucose and, the increase of plasma glucose, and may, as a consequence, be utilized by species only in emergence situations.
Keywords: Fisiologia respiratória; Loricariidae; Peixe respiração; Superfície respiratória; Hemoglobina; Metabolismo; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA DA RESPIRACAO